Thermal techniques and their applications: Taking advantage of the “heat of the moment” - de Moraes, Alanna Silveira; de Almeida Furtado, Leonardo; Maciel Buzzetti, Paulo Henrique; de Cássia da Silva, Rita [UNESP]; Semaan, Felipe Silva (My University, 2017)
Undoubtedly, the interactions between matter and heat have changed both the world and humanity’s evolution. From the discovery of fire to our current reality, passing through all of scientific history, heat control has allowed to protect ourselves, process food, manipulate metals, change and sterilize materials, accelerate synthetic pathways or even extract desired information about certain materials, such as thermal stability, melting points and purity, among others. In this context, this chapter aims to present a concise but complete briefing on the early history and fundamental concepts concerning thermal analysis, beginning at thermogravimetric measurements (TGA), differential thermal analysis (DTA), high-resolution thermogravimetric analysis (Hi-Res TGA®) and evolved gas analysis (EGA) by hyphenated thermogravimetric analysis-infrared spectroscopy (TGA-IR). These techniques extract different information from small solid samples, usually without prior sample pre-treatment. Mass changes are monitored by TGA while temperature differences between samples and references are registered by thermocouples in DTA. Different optimization strategies or even new equipment and algorithms provide higher resolution profiles (Hi-Res TGA) when compared to those found by classical TGA, becoming an exceptional tool to elucidate complex thermal mechanisms. Complimentary information regarding evolved gas can be reached by means of infrared assessment of release gas (TGA-IR). Experimental tips and hints will be extracted from real cases, and presented here in an instructive manner, while theory and practical recommendations will be given didactically, in order to provide readers with a better understanding of thermal procedures, from planning to interpretation of obtained data.